Estimating the Potential of Building Integration and Regional Synergies to Improve the Environmental Performance of Urban Vertical Farming - Martin, Michael; Weidner, Till; Gullström, Charlie (Frontiers in Sustainable Food Systems, 2022)
Vertical farms have expanded rapidly in urban areas to support food system resilience. However, many of these systems source a substantial share of their material and energy requirements outside their urban environments. As urban areas produce significant shares of residual material and energy streams, there is considerable potential to explore the utilization of these streams for urban agriculture in addition to the possibility of employing underutilized urban spaces in residential and commercial buildings. This study aims to explore and assess the potential for developing more circular vertical farming systems which integrate with buildings and utilize residual material and energy streams. We focus on the symbiotic development of a hypothetical urban farm located in the basement of a residential building in Stockholm. Life cycle assessment is used to quantify the environmental performance of synergies related to energy integration and circular material use. Energy-related scenarios include the integration of the farm's waste heat with the host building's heating system and the utilization of solar PV. Circular material synergies include growing media and fertilizers based on residual materials from a local brewery and biogas plant. Finally, a local pick-up system is studied to reduce transportation. The results point to large benefits from integrating the urban farm with the building energy system, reducing the vertical farm's GHG emissions up to 40%. Synergies with the brewery also result in GHG emissions reductions of roughly 20%. No significant change in the environmental impacts was found from the use of solar energy, while the local pick-up system reduces environmental impacts from logistics, although this does not substantially lower the overall environmental impacts. However, there are some trade-offs where scenarios with added infrastructure can also increase material and water resource depletion. The results from the synergies reviewed suggest that proximity and host-building synergies can improve the material and energy efficiency of urban vertical farms. The results provide insights to residential building owners on the benefits of employing residual space for urban food provisioning and knowledge to expand the use of vertical farming and circular economy principles in an urban context.